2014
DOI: 10.3389/fnana.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal extension in site of origin for cortical calretinin neurons in primates

Abstract: The vast majority of cortical GABAergic neurons can be defined by parvalbumin, somatostatin or calretinin expression. In most mammalians, parvalbumin and somatostatin interneurons have constant proportions, each representing 5–7% of the total neuron number. In contrast, there is a threefold increase in the proportion of calretinin interneurons, which do not exceed 4% in rodents and reach 12% in higher order areas of primate cerebral cortex. In rodents, almost all parvalbumin and somatostatin interneurons origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 114 publications
(186 reference statements)
6
69
0
1
Order By: Relevance
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallmentioning
confidence: 73%
See 1 more Smart Citation
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallmentioning
confidence: 73%
“…The increase in the proportion of GABAergic neurons in primate neocortex is thought to primarily reflect an increase in the vasoactive intestinal polypeptide (VIP)/calretinin (CR)-expressing subtype (Hansen et al 2013;Dzaja et al 2014;Hladnik et al 2014;Barinka et al 2015), which arises in the caudal and lateral ganglionic eminences (CGE/LGE) and preferentially occupies superficial cortical layers (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010). In humans, half or more of neocortical GABAergic neurons may derive from the CGE (Hansen et al 2013), whereas in mice this number is closer to~30% (Miyoshi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the actual proportions of OSVZ generated interneurons-as opposed to subpallium-derived interneurons-is still debated Ma et al, 2013), reports suggest that the OSVZ is the major production site of calretinin neurons (Hladnik et al, 2014), which represent the predominant category of interneurons in primates (12%) as opposed to rodents (4%). Thus, the OSVZ may serve as a permissive niche for the proliferation of GABAergic precursors.…”
Section: Diversity Of Basal Precursor Typesmentioning
confidence: 99%
“…A later study found that a subpopulation of Emx1 -lineage cells originating in the pallium migrates to the developing striatum during early prenatal development [41] and differentiates primarily into DARPP-32-positive medium-sized spiny neurons but also a small number of CR-positive (but no other) striatal interneurons [42]. The pallium has been proposed as the main source of CR+ interneurons in the primate neocortex–and the explanation for the specific expansion of this interneuron subtype in primates [43,44]. It is not yet clear whether any or all adult-born striatal interneurons derive from the Emx-1 lineage in the normal rodent, but these young neurons would represent a small proportion of the interneurons or Emx-1-derived neurons in the rodent striatum and could easily be overlooked.…”
Section: The Origin Of New Striatal Neuronsmentioning
confidence: 99%
“…Whether generation of striatal interneurons is greater in human than in rodents is less clear. Intriguingly, the proportion of striatal and neocortical interneurons that are CR-positive greatly increases across species, from less than 1% in rodents to 10% in humans, where they represent the predominant interneuron subtype [43,44,61,62]. The size of the vSVZ-derived ICj is also substantially greater in primates than in rodents [17,63].…”
Section: Relative Rates Of Neurogenesis Across Speciesmentioning
confidence: 99%